2017
DOI: 10.1080/13658816.2017.1349318
|View full text |Cite
|
Sign up to set email alerts
|

Color map design for visualization in flood risk assessment

Abstract: Visualizations of flood maps from simulation models are widely used for assessing the likelihood of flood hazards in spatial planning. The choice of a suitable type of visualization as well as efficient color maps is critical to avoid errors or bias when interpreting the data. Based on a review of previous flood uncertainty visualization techniques, this paper identifies areas of improvements and suggests criteria for the design of a task-specific color scale in flood map visualization. We contribute a novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…Although there are several studies that assess the design of flood maps, such as the most appropriate colour scheme for depicting floodplains (Seipel and Lim, 2017), this study focused on key characteristics that international scholars highlight as important for public risk communication. In this context, the purpose of the map is to inform the public about flood risks and motivate individuals to take precautionary actions (Hagemeier-Klose and Wagner, 2009).…”
Section: Quality Evaluation Frameworkmentioning
confidence: 99%
“…Although there are several studies that assess the design of flood maps, such as the most appropriate colour scheme for depicting floodplains (Seipel and Lim, 2017), this study focused on key characteristics that international scholars highlight as important for public risk communication. In this context, the purpose of the map is to inform the public about flood risks and motivate individuals to take precautionary actions (Hagemeier-Klose and Wagner, 2009).…”
Section: Quality Evaluation Frameworkmentioning
confidence: 99%
“…In Canada, Stevens and Hanschka (2014) collected flood hazard maps from every municipality in the province of British Columbia and evaluated them based on 32 good mapping practices, such as whether they included a legend, indicated the floodway boundary, included the flood elevation for different probabilities, and showed the boundaries of individual property parcels. They found that only 43 % of municipalities possessed a flood hazard map and most of these maps were of poor quality for land use decision-making, with no map containing more than 15 of the 32 assessment criteria (i.e., > 47 %).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are several studies that assess the design of flood maps, such as the most appropriate colour scheme for depicting floodplains (Seipel and Lim, 2017), this study focused on key characteristics that international scholars highlight as important for public risk communication. In this context, the purpose of the map is to inform the public about flood risks and motivate individuals to take precautionary actions (Hagemeier-Klose and Wagner, 2009).…”
Section: Quality Evaluation Frameworkmentioning
confidence: 99%
“…Linear interpolation and curve interpolation are commonly used methods to create sequential color schemes. 14,15,19,[22][23][24] Here, we choose the linear interpolation, the most widely used method, as our interpolation method and select the CIELAB color space, which is perceptually uniform, as our color space. Through linear interpolation, sequential color schemes can be generated along lines in the CIELAB color space.…”
Section: Interpolation Of Sequential Color Schemesmentioning
confidence: 99%
“…15 These methods assume that the starting color and ending color have already been given or selected. Then, intervening colors can be generated using interpolation algorithms that include linear, 19,[22][23][24] curve, 14,25 and inverse distance weighting interpolation algorithms. 26 For example, Seipel 23 selected blue and gray as the starting color and ending color, respectively.…”
Section: Introductionmentioning
confidence: 99%